Salinity footprint on anoxic-aerobic sequential moving bed reactors during petroleum refinery wastewater treatment: Effects on the dominant species. (October 2020) - Mallick, Subrat Kumar; Chakraborty, Saswati
Graphical abstract: Highlights: Organics removal deteriorated with increase in NaCl in anoxic reactor. Sulfide removal remained intact in anoxic reactor. Organics and NH4+-N removal decreased beyond 30 g/L of NaCl in aerobic reactor. Pseudomonas aeruginosa SC2013 tolerated salinity in anoxic biomass. Lysinibacillus sp. H200-150 tolerated salinity in aerobic biomass. Abstract: Consequence of increased NaCl (0−45 g/L) on the performance of anoxic (A1) - aerobic (A2) sequential moving bed reactors operated in series was examined while treating synthetic petroleum refinery wastewater. Influent wastewater was a concoction of phenol (750 mg/L), S 2− (750 mg/L), crude oil (300 mg/L), NO3 –N (1000 mg/L), NH4 + -N (350 mg/L) and emulsifier (0.2 mM) along with varied NaCl. Removal of organics deteriorated in A1 (60 h HRT) with rise in NaCl and complete removal of residual organics and NH4 + -N was achieved in A2 (20 h HRT) up to 30 g/L of NaCl at total 80 h HRT. Effect of salinity was never observed for S 2− removal in A1. Increase in sloughing, decrease in SRT and biomass activity were the outcomes of increased NaCl. Pseudomonas aeruginosa SC2013 and Lysinibacillus sp. H200−150 tolerated higher salinity in A1 and A2, respectively. Complete restoration of the reactor performance was achieved after withdrawal of NaCl.